2012
DOI: 10.1074/jbc.m111.287748
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Sup35 by Aggregates of huntingtin Fragments Causes Toxicity of [PSI+] Yeast

Abstract: Background: Yeast have been used to study hungtingtin toxicity.Results: Both HttQ103 and HttQP103 are toxic in yeast with [PSI+] prion. This toxicity is markedly rescued by a Sup35 fragment.Conclusion: Sequestration of the essential protein, Sup35, contributes to Htt toxicity in yeast.Significance: This research demonstrates the complex nature of Htt toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…As a result, the association of molecular chaperones of the Hsp70 and Hsp90 systems with the polyQ aggregates was enhanced, and their ability to sequester nuclear proteins was strongly reduced. Protein sequestration into aggregates may lead to an impairment of multiple key cellular pathways and is considered an important mechanism of aggregate toxicity (7,9,10,32,50,(53)(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the association of molecular chaperones of the Hsp70 and Hsp90 systems with the polyQ aggregates was enhanced, and their ability to sequester nuclear proteins was strongly reduced. Protein sequestration into aggregates may lead to an impairment of multiple key cellular pathways and is considered an important mechanism of aggregate toxicity (7,9,10,32,50,(53)(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have revealed that the sequestration is mediated by coaggregation of polyQ tracts (53)(54)(55). Cooperative polyQ-polyQ interactions also prompt aggregation of the polyQ proteins.…”
Section: Specific Interaction Is Vital For the Sequestration Of Usp22 Bymentioning
confidence: 99%
“…For example, polyQ-expanded Htt aggregation and its associated toxicity are strongly enhanced by overexpression of polyQN-rich proteins or by the presence of the endogenous yeast prions [ RNQ + ] and [ PSI + ] (Meriin et al, 2002, Duennwald et al, 2006a, Kochneva-Pervukhova et al, 2012, Gong et al, 2012, Zhao et al, 2012, Gokhale et al, 2005, Giorgini et al, 2005), and this enhancement corresponds to co-localization of the aggregating proteins (Meriin et al, 2003, Duennwald et al, 2006a, Gong et al, 2012). Given the ability of polyQ-expanded Htt to induce aggregation of Sup35 (Kochneva-Pervukhova et al, 2012, Urakov et al, 2010) and the essential function of Sup35 in translation termination (Ter-Avanesyan et al, 1993), several groups explored the possibility of Sup35 sequestration as a mechanism for Htt toxicity in yeast (Gong et al, 2012, Kochneva-Pervukhova et al, 2012, Zhao et al, 2012). In the presence of [ RNQ + ] alone, polyQ-expanded Htt clearly induced aggregation of Sup35 (Gong et al, 2012, Kochneva-Pervukhova et al, 2012), but expression of the Sup35 functional domain was efficient in suppressing toxicity in one study (Kochneva-Pervukhova et al, 2012) but not in another (Gong et al, 2012).…”
Section: Polyq Toxicity In Yeastmentioning
confidence: 99%
“…In the presence of [ RNQ + ] alone, polyQ-expanded Htt clearly induced aggregation of Sup35 (Gong et al, 2012, Kochneva-Pervukhova et al, 2012), but expression of the Sup35 functional domain was efficient in suppressing toxicity in one study (Kochneva-Pervukhova et al, 2012) but not in another (Gong et al, 2012). However, in the presence of both [ RNQ + ] and [ PSI + ], the toxicity of polyQ-expanded Htt is efficiently suppressed by expression of the functional domain of Sup35 (Gong et al, 2012, Zhao et al, 2012). Thus, while either type of aggregate alone is benign, the combination of polyQ and prion aggregates creates an imbalance presumably between the aggregation assembly pathway and cellular protein quality control pathways that promotes sequestration of Sup35 and thereby toxicity (Figure 1b).…”
Section: Polyq Toxicity In Yeastmentioning
confidence: 99%
See 1 more Smart Citation